ANALISIS KEBUTUHAN PARKIR UNTUK INDUSTRI PAKAIAN JADI PT. MOD INDO - PRINGAPUS - Wibowo Wibowo; Hartopo Hartopo; Totok Apriyanto (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
PT. MOD Indo Pringapus is one of the garment industry players located in Pringapus District, their business activity is the manufacture of apparel with a market share of 100% exports to America. PT. MOD Indo is located on Jalan Raya Pringapus Candirejo in the Bumi Wahyu Warehousing Complex, Kali Kuning neighborhood, Pringapus Village, Pringapus District, Semarang Regency. PT. MOD Indo has an area of 21,117 m2, a total building area of 15,296 m2, and a total area of 5,821, m2 of open land. With number of employees reaching 1250 employees, the need for parking spaces for employees, raw material vehicles, and production transportation vehicles needs to be provided with a suitable place & adequate. The current condition based on the author's observations, there are still many parking arrangements that are not in place due to the very limited condition of the land and parking buildings. Seeing these conditions, it is necessary to plan for the provision of parking facilities. From the results of the survey on the availability of parking at the location, the parking capacity that is owned can accommodate 25 car parking lots and 800 motorbike parking lots. The parking area used is approximately 1500 m2. The parking requirements that need to be provided are 50 SRP for Cars, 192 SRP for Motorcycles and 10 SRP for Trucks, while the required land area includes circulation of 1,674.4 m2. Based on the results of the analysis above and the description of the next few years where the rate of vehicle development is estimated at around 10% per year, the authors can conclude that the performance of parking spaces for current conditions does not meet the needs of existing users so that there needs to be improvements in parking space arrangements including the addition of new parking spaces.